A lightweight heterogeneous hybrid mobile cloud computing framework for compute-intensive mobile applications / Zohreh Sanaei Moghaddam - Moghaddam, Zohreh Sanaei (2014)
The state-of-the-art Mobile Cloud Computing (MCC) paradigm has gained a momentous ground to mitigate mobile devices’ shortcomings (i.e., computing and energy) by outsourcing resource-intensivemobile tasks to the cloud. Researchers have proposed solutions for compute-intensive mobile applications by leveraging varied types of cloud-based resources, particularly coarse, medium, and fine granular cloud resources. Coarse-grained cloud resources feature high scalability and low locality that originates communication latency, fine-grained resources offer low scalability and high locality that leads to computation latency, and medium-grained resources provide medium scalability and locality breeding communication and computing latency. Such communication and computation latencies negatively impact on energy efficiency and response time of compute-intensive mobile applications leading to mobile application performance degradation. As a result, leveraging vertical heterogeneous granular cloud resources creates a bottleneck of limited computing and communication capabilities which results in increased response time and energy consumption. Vertical heterogeneity rises within one type of granular resources, like coarse or fine. This research is undertaken with the aim to obtain efficient computation outsourcing for compute-intensive mobile applications using horizontally heterogeneous granular cloud-based resource. Horizontal heterogeneity happens across varied types of granular resources, like coarse and fine. Using a series of benchmarking experiments we investigate the impacts of computation and communication latencies of granular resources on round-trip time and energy consumption of compute-intensive mobile applications and establish the research problem. Moreover, we propose a lightweight heterogeneous hybrid MCC framework for compute-intensive mobile applications that aims to reduce response time and prevent energy dissipation on mobile devices. We analyse execution of a compute-intensive mobile application considering two performance metrics, namely Round-Trip Time (RTT) and Energy Consumption (EC) in two execution models of local and hybrid. We evaluate performance of the proposed framework in real environment and validate the results through statistical modelling. The results of RTT analysis advocates average of 93.5% RTT saving in hybrid mode compared with local mode and the EC analysis results testify average of 94% energy saving in hybrid mode compared with local mode. The results express that utilizing heterogeneous hybrid cloud-based computing resources can significantly reduce RTT and EC of mobile device in hybrid mode compared with local mode execution.